Lithuanian Jewish in 1941-1945: continuation of holocaust in Stutthoff concentration camp (1) - Buchaveckas, Stanislovas (Genocidas ir rezistencija, 2020)
At the beginning of the Second World War, the Stutthof concentration camp was established on the territory of the Nazi Germany-occupied Free City-State of Danzig (Gdansk) (existed from 1920 to 1939) – a place of suffering and death of Lithuanians as well as Jewish Lithuanian citizens. However, until 2020, no comprehensive analytical work on the Lithuanian Judaica of the tragic events of Stutthof was published. This follow-up article will therefore attempt to fill at least part of this gap. Especially that the Government of the Republic of Lithuania, implementing the Resolution of the Seimas of the Republic of Lithuania of 10 May 2018 “On Declaring 2020 the Year of Vilnius Gaon and the History of the Jews of Lithuania”, has planned a number of events dedicated to this occasion this year and encouraged the research of problems related to the tragedy of the Jews of Lithuania during World War II, the development of publishing activities and the writing of various articles.
Keywords: german occupation; jews; Holocaust; Stutthof; concentration camp